Emergency Medicine Physicians Success Rate in Reducing Anterior Shoulder Dislocations: A Retrospective Observational Study - Mohammed Alshalhoub; Hamad Alawlah; Mohammed Alageel; Lina Alhumaid; Dana Altamimi; Mohammed Benmeakel (Saudi Journal of Emergency Medicine)
Background: Shoulder dislocations are common occurrences, with anterior shoulder dislocations being the most prevalent. Various reduction techniques are employed, but success rates and influencing factors remain variable. This study aims to evaluate the success rate of anterior shoulder reductions performed by emergency physicians, as well as factors contributing to reduction failure and extended emergency department (ED) stay.